1991
DOI: 10.1017/s0025315400051717
|View full text |Cite
|
Sign up to set email alerts
|

Image Analysis of Faecal Material Grazed Upon by Three Species Of Copepods: Evidence For Coprorhexy, Coprophagy and Coprochaly

Abstract: Experiments involving three species of copepods(Acartia clausi Giesbrecht 1889, Pseudocalanus elongatus Boeck 1872 and Calanusfinmarchicus Gunnerus 1765) incubated with freshly produced copepod faecal material were conducted and analyzed using automatic image analysis. For two species (A. clausi and C. finmarchicus) the bulk of faecal material was not ingested but was fragmented. This process, coprorhexy, was accompanied by a shift toward smaller particles in the particle size-spectrum. Increases in total volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(78 citation statements)
references
References 34 publications
1
77
0
Order By: Relevance
“…In addition, newly formed pellets could be easily distinguished from older pellets originally in aggregates because new pellets were compact and had intact membranes. Copepods are known to ingest their own or other species' fecal pellets (Noji et al 1991 Treatments experiments, they may have ingested some of them during the course of the experiment. However, coprophagy and coprorhexy were not evident, since pellets examined after experiments were not fragmented and were still intact in membranes.…”
Section: Discussion Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, newly formed pellets could be easily distinguished from older pellets originally in aggregates because new pellets were compact and had intact membranes. Copepods are known to ingest their own or other species' fecal pellets (Noji et al 1991 Treatments experiments, they may have ingested some of them during the course of the experiment. However, coprophagy and coprorhexy were not evident, since pellets examined after experiments were not fragmented and were still intact in membranes.…”
Section: Discussion Of Methodsmentioning
confidence: 99%
“…Production of fecal pellets clearly demonstrates feedlng, and fecal pellets can be recovered and measured to quantify egestion, which can then be converted to ingest~on lf the assimilation efficiency is known. The disadvantage of this technique is that animals may ingest or break apart their own fecal pellets, resulting in an underestimation of feedin.g rate (Noji et al 1991). The majority of experiments reported here are fecal pellet production experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Fecal pellets were visibly opened, macerated and even cut in half during rejection. Eucalanus pileatus females have also been observed to inflict damage to fecal pellets during rejection (Paffenhöfer & Van Sant 1985) and Acartia clausi and Calanus finmarchicus were observed to fragment rather than ingest fecal pellet material (Noji et al 1991).…”
Section: Processes Governing the Clearance Of Fecal Pelletsmentioning
confidence: 99%
“…Both studies observed rejection of fecal pellets. Thus, coprorhexy rather than coprophagy may account for the role of some copepods in reducing the vertical flux of fecal pellets, by turning pellets into smaller, slower-sinking fragments, which are more prone to microbial degradation (Noji et al 1991). Evidence of coprorhexy has been found in the field where fecal pellets were observed to be converted into small, amorphous particles (Knappertsbusch & Brummer 1995, Suzuki et al 2003.…”
Section: Ecological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation